HUBUNGAN ANTARA KARAKTERISTIK INDIVIDU UNIT KERJA DAN FAKTOR ERGONOMI DENGAN KELUHAN KESEHATAN DI INDUSTRI KECIL SEPATU KOTA MOJOKERTO - Margaretta Frizka; Tri Martiana (Universitas Airlangga, 2017)
Study of health complaint for shoes makers have been made in UD Wardana Mojokerto City. The purpose of the study were to identify individual and enviromental factor associated with health complaint. This study was an observational descriptive with cross sectional approach. The respondents were all shoes makers that worked in UD Wardana Mojokerto city (N=28). Variables of this study were individual caracteristics (age, duration of employments, regular physical exercise, and smoking habit), work section, and ergonomic factors (work posture, static sitting, posture of sitting, static standing, and posture of standing). The data were collected and analyzed with chi – square and contingency coefficientThe results that most of the respondents were aged 19-27 years (46,43%),duration of employment 1-5 years (46,43%) didn’t take regular physical exercise (68,57%), and non smoker (78,57%). There were strong association between respiration complaint with age (C= 0,535), duration of employment (C= 0,509). Musculosceletal complaint with static sitting (C= 0,544), static standing (C= 0,559), and body posture (C= 0,559). From the findings, It is concluded that shoes makers have risk of musculoskeletal and respiratory complaints.Keywords: Ergonomic factors, health complaints, shoes makers, individual characteristics